A universal mathematical model on the gas dependence of the tribological properties of films. (January 2022) - Chen, Lin; Wu, Jian; Lu, Zhibin; Shang, Lunlin; Zhang, Guangan; Xue, Qunji
Abstract: A mathematical model based on the adsorption and removal of gas species is developed to describe the friction coefficient of films in atmosphere. Gas adsorption process in different stages conforms to the adsorption kinetic equation of corresponding stage. Furthermore, the relationship between the two adsorption stages is revealed with a new adsorption kinetic equation, providing the basis to tailor sliding interface. Highlights: Mathematical model was built to describe friction coefficient of film in gas. The monolayer and multilayer gas adsorption processes during sliding were reported. The adsorption layers were related by a new adsorption kinetic equation.